Chemical characteristics and toxicity of particles from residential biomass combustion - Vicente, Estela Alexandra Domingos (2022)
Biomass combustion for residential heating is recognised as an important source of particulate matter, not only in the ambient air, but also inside the dwellings. Exposure to biomass burning particles has been linked to a vast array of adverse health effects. The physical and chemical properties of inhaled particles are thought to greatly affect the biological responses. Over the years, many studies have focused on emission source profiles of residential biomass combustion. However, with the advent and growing market share of new small-scale appliances automatically fed with compressed biofuels, research efforts need to be devoted to the characterisation of emissions from these appliances either from new commercially available pellets or from pellets made from potentially relevant raw materials. Despite the wealth of publications on emissions and composition of particles from residential biomass combustion, the impact of this source on the indoor air quality has been scarcely studied, especially with regard to the chemical and toxicological characteristics of the particles. The two main objectives of this thesis were: i) to obtain chemical and toxicological profiles for pellet-fuelled heating systems, and ii) to evaluate the impact of traditional appliances on indoor air quality, properties of particulate matter, deposited dose in the respiratory tract and biological responses. For the fulfilment of the first objective, four types of pellets were selected (two brands of ENplus A1 certified pellets, one brand of non-certified pellets, and laboratory-produced acacia pellets) to carry out experiments in a laboratory combustion facility to determine emission factors of gaseous compounds and particulate matter (PM10). To achieve the second objective, particulate samples were collected in two households equipped with distinct combustion appliances (open fireplace and woodstove) in the absence of other indoor sources. The dose of inhaled indoor particles deposited in the human respiratory tract was estimated using an exposure dose model (ExDoM2). The chemical composition of PM10 from both laboratory experiments and residential microenvironments was analysed for water soluble inorganic ions, organic and elemental carbon and detailed organic speciation. Additionally, in samples collected indoors, major and trace elements were also determined. A battery of in vitro assays was used to assess the ecotoxicity, cytotoxicity and mutagenicity of the PM10 samples. The results obtained from the laboratory measurements indicated that the alternative woody raw material selected for pelletising contributed to a dramatic increase in particulate emissions, with distinctive chemical properties and increased toxicological potential. It was observed that even certified material does not always meet emission requirements set by the Ecodesign directive. Particles from pellet combustion were mainly composed of water soluble inorganic constituents. The carbonaceous fraction of particulate samples from commercial pellets was dominated by elemental carbon, while organic carbon was the most abundant constituent in samples from the combustion of acacia pellets. The results showed that particles from acacia pellets were the most ecotoxic and cytotoxic, while mutagenicity was not detected for any biofuel. In the sampling campaign carried out in residential microenvironments while using different combustion devices, higher exposures, higher doses in the human respiratory tract and higher toxicity of the particles collected during the operation of the open fireplace were observed, as a result of the lower combustion efficiency. When using this combustion equipment, a higher increase in particulate matter levels (over 12 times compared to background concentrations) was registered compared to that measured with the woodstove (2-fold increase). The carbonaceous material accounted for a PM10 mass fraction of about 44% in samples from the room equipped with fireplace, while the woodstove operation almost halved the total particulate carbon content. Water soluble ions and trace elements showed variable contributions to the mass of the indoor particles and were generally higher during the operation of the woodstove. Several chemical markers of biomass combustion were detected in both residential microenvironments, highlighting the input of this source to indoor particles. The bioreactivity assessment showed that particles emitted by the fireplace were the most ecotoxic and cytotoxic, while mutagenicity was not detected in any of the tested samples. Combustion-related organic compounds in indoor particles, such as polycyclic aromatic hydrocarbons, displayed significant correlations with the increase in toxicity. In view of the results obtained, homeowners should be encouraged to upgrade the wood burning technology in order to reduce the products of incomplete combustion inside their dwellings.